Food Security and Consumer Protection: An Analysis of Sanctions on the Sale of Expired Food Products from the Perspective of Islamic Criminal Law and Positive Law in Indonesia - Prasetiyo, Yogi; Yazid, Imam (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
The Sale of Expired Food Products: A Serious Violation That Poses Risks to Consumers' Physical and Psychological Health. This study aims to analyze the sanctions on selling expired food products from the perspective of Islamic Criminal Law and Law No. 8 of 1999 on Consumer Protection. Using a normative research method and comparative analysis, the study finds that Islamic Criminal Law emphasizes the moral aspect, such as the prohibition against causing harm to others (la darbar wa la dinar), with penalties adjusted according to intent and the impact of the violation, such as visas, diyat, or ta'zir. On the other hand, Law No. 8 of 1999 emphasizes legal certainty through criminal sanctions to protect consumers. The study highlights the similarities between the two legal systems in consumer protection but also notes the differing approaches, with Islamic Criminal Law focusing more on moral responsibility. At the same time, positive law emphasizes a deterrent effect legally. This research is expected to contribute to improving consumer protection regulations that are more comprehensive and just